2018
DOI: 10.1080/14693062.2018.1470963
|View full text |Cite
|
Sign up to set email alerts
|

The impact of compensatory measures on public support for carbon taxation: an experimental study in Sweden

Abstract: This study aims at better understanding how, and to what extent, perceptions of a policy instrument's distributional effects impact on policy support, focusing on the case of CO 2 taxes on petrol in Sweden. Through a large-scale (N = 5000) randomized survey experiment with a 2 × 3 factorial design, the extent to which perceptions of fairness determine attitudes to a suggested increase of the Swedish CO 2 tax is explored. Furthermore, the study considers whether these effects change with the level of the sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 70 publications
4
52
0
2
Order By: Relevance
“…Although the popularity of carbon taxation could be increased by compensating increased costs with income redistribution (Callan et al, 2009;Hsu, 2016;Jagers et al, 2019) or by providing information about the positive effects of carbon taxation (Carattini et al, 2017), the fear of rising costs is likely to decrease the support for increasing energy taxation. This applies especially to people who do not consider climate change to be a major risk (Frondel et al, 2017).…”
Section: Fossil Fuel Taxation and Nordic Countriesmentioning
confidence: 99%
“…Although the popularity of carbon taxation could be increased by compensating increased costs with income redistribution (Callan et al, 2009;Hsu, 2016;Jagers et al, 2019) or by providing information about the positive effects of carbon taxation (Carattini et al, 2017), the fear of rising costs is likely to decrease the support for increasing energy taxation. This applies especially to people who do not consider climate change to be a major risk (Frondel et al, 2017).…”
Section: Fossil Fuel Taxation and Nordic Countriesmentioning
confidence: 99%
“…In addition, a number of studies point towards public suspicion that carbon taxes will not effectively discourage high-carbon behaviour (Hsu, Walters, & Purgas, 2008;Kallbekken & Saelen, 2011;Steg, Dreijerink, & Abrahamse, 2006) as well as a concern that the purpose of introducing a carbon tax is primarily to increase government revenues, rather than to positively impact the climate (Klok, Larsen, Dahl, & Hansen, 2006). These and other studies all highlight the significance of policy design for increasing support for CO 2 taxes, in terms of the tax rate itself, revenue use, and combining the tax with other measures (see Bento, Franco, & Kaffine, 2009;Dresner, Dunne, Clinch, & Beuermann, 2006;Eriksson, Garvill, & Nordlund, 2008;Hammar & Jagers, 2006;Hsu et al, 2008;Jagers, Martinsson, & Matti, 2018;Sumner, Bird, & Dobos, 2011). Here, we acknowledge the possible effect of policy-specific beliefs on policy attitudes, both as a CO 2 tax might be perceived to have direct negative consequences for the economy of the country (and thus for the citizens of that country), and since the economic consequences might be perceived as affecting the own country more than other comparable economies.…”
Section: Theorizing Public Support For Co 2 Taxesmentioning
confidence: 99%
“…Initial research in this vein has revealed the willingness of U.S. citizens to accept carbon taxes ( 17 ). Jagers et al ( 11 ) showed that Swedish citizens are more likely to accept a carbon tax on car fuel if combined with an income tax cut. Carattini et al ( 18 ) found that Swiss citizens are more likely to support energy taxes when revenue recycling is included.…”
Section: Introductionmentioning
confidence: 99%